Neutron diffraction analysis of stresses in an in-plane biaxially-fatigued stainless steel sample of cruciform geometry - Taran, Y; Balagurov, A; Schreiber, J; Korsunsky, A (2008)
An ex-situ in-plane biaxial low cycle fatigued sample of cruciform geometry made from austenitic stainless steel AISI 321 H was studied with the help of neutron diffraction strain scanning and also in-situ uniaxial loading using a stress rig on the FSD stress-diffractometer at the IBR-2 pulsed nuclear reactor (Dubna). The objectives of the experiment were to measure the macroscopic and microscopic residual stresses, crystallographic phase composition and the mechanical characteristics of the alloy under fatigue conditions. To the best of our knowledge, no neutron diffraction investigations of structural alloys subjected to biaxial loading have previously been reported. Experimental data interpretation and analysis are presented and discussed.